2015
DOI: 10.1161/circresaha.115.307004
|View full text |Cite
|
Sign up to set email alerts
|

Bromodomain-Containing Protein 4

Abstract: P ulmonary arterial hypertension (PAH) is an obstructive vascular pathology affecting the small pulmonary arteries (PAs). It is characterized by enhanced inflammation, vasoconstriction, and proliferation/apoptosis imbalance within the artery wall, leading to increased pulmonary vascular resistance, right ventricular (RV) failure and death.1 PAH is a rare disease with an estimated prevalence of 15 to 50 cases/million 2 and its prevalence is thought to be highly underestimated [3][4][5][6] because of lack of sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
103
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 150 publications
(112 citation statements)
references
References 52 publications
8
103
0
1
Order By: Relevance
“…BRD4 inhibition was also associated with improvements in hemodynamic measurements (mean pulmonary artery pressures of 16, 54, 50, 29, 54, and 36 mm Hg for Control, Sugen-PAH, Sugen-PAH+scrambled siRNA, Sugen-PAH+siBRD4, Sugen-PAH+dimethyl sulfoxide, and Sugen-PAH+JQ1, respectively) and lung vascular remodeling. 12 We also observed that siBRD4-treated rats exhibited over 50% knockdown of BRD4-positive cells within their coronary arteries ( Figure IID in the online-only Data Supplement). This may be attributable to the decrease in IL-6 levels within heart tissues, as shown below, or through other feedback loops that still need to be investigated.…”
Section: Brd4 Inhibition Shows Beneficial Effects On the Coronary Cirmentioning
confidence: 61%
See 4 more Smart Citations
“…BRD4 inhibition was also associated with improvements in hemodynamic measurements (mean pulmonary artery pressures of 16, 54, 50, 29, 54, and 36 mm Hg for Control, Sugen-PAH, Sugen-PAH+scrambled siRNA, Sugen-PAH+siBRD4, Sugen-PAH+dimethyl sulfoxide, and Sugen-PAH+JQ1, respectively) and lung vascular remodeling. 12 We also observed that siBRD4-treated rats exhibited over 50% knockdown of BRD4-positive cells within their coronary arteries ( Figure IID in the online-only Data Supplement). This may be attributable to the decrease in IL-6 levels within heart tissues, as shown below, or through other feedback loops that still need to be investigated.…”
Section: Brd4 Inhibition Shows Beneficial Effects On the Coronary Cirmentioning
confidence: 61%
“…We observed that BRD4, which is increased in the lungs of patients with PAH, 12 is also overexpressed in their coronary arteries and is responsible, at least in part, for triggering vascular remodeling processes and increasing the risk of these patients to develop MVD or CAD. We showed that coronary arteries of patients with PAH, regardless of their location within the heart (RV or left ventricle), had greater wall thickness ( Figure 1A; Figure IA in the online-only Data Supplement), exhibited increased inflammation (IL-6, Figure 1D), sustained DNA damage ( Figure 1F), and significantly more BRD4-expressing cells (Figure 2A; Figure IIA in the online-only Data Supplement).…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations